Persepsi ketua panitia mata pelajaran terhadap program perkembangan staf di sekolah menengah di bahagian Samarahan, Sarawak - Mohamad Syariff Affendy, Bin Matjeraie. (1998)
Staff Development Programme (SDP) is not fully implemented in schools. Does the Heads of Subject Panel (HSP) perceptions of the SDP influence the efficiency of SDP implementation in schools? This study aims to study the problem statement based on secondary schools in Samarahan Division, Sarawak. The conceptual framework of this study is based on the assumption that the efficiency of SDP is depended on four factors: Needs for SDP; human resource supports; implementation process; and support facilities like material, place and time. Questionnaire was used to collect information regarding this study from 156 HSP in secondary schools in Samarahan Division, Sarawak. The finding of this study showed that the HSP had positive perceptions towards SDP. However, they were still not satisfied with the present implementation of the SDP.